Semi-Implicit Difference Scheme for a Two-Dimensional Parabolic Equation with an Integral Boundary Condition - Jakubėlienė, Kristina; Čiupaila, Regimantas; Sapagovas, Mifodijus (Mathematical Modelling and Analysis, 2017)
In this paper, we consider a finite difference method for a class of twodimensional parabolic equations with integral boundary conditions. The semi-implicit difference scheme is considered. The stability of difference scheme is proved using the properties of the M-matrices, particularly, the regular splitting of an M-matrix. The numerical results of some examples are presented, that approve our theoretical investigations.